Pengambilan Keputusan Dalam Menyelesaikan Pembukaan Rekening Online Bermasalah Melalui Mobile Banking Pada Bank Syariah Indonesia KCP Simpang Limun - Adelia Natasya Daulay (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Opening an online account is a banking service provided by the bank to make it easier for customers who want to open an account at a bank. However, in operation, there are also those who experience problems opening online accounts. The purpose of this research is to determine the decision-making process of Bank Syariah Indonesia KCP Simpang Limun in resolving the opening of online accounts for problematic customers. The matters described include the factors causing online account openings, the bank's decision-making mechanism in resolving problematic online account openings. This research uses qualitative methods while the data collection methods used are interviews, observation and documentation. The results of this research indicate that to overcome problems in opening online accounts for customers of Bank Syariah Indonesia KCP Simpang Limun by authorizing the customer's account through the bank supervisor. Before opening an online account, customers should pay attention to the condition, both of the smartphone used and the data that will be used registered.